2019
DOI: 10.1097/md.0000000000016900
|View full text |Cite
|
Sign up to set email alerts
|

Closed rupture of extensor tendon resulting from untreated Kienböck disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Two reviews have previously summarized the characteristics of extensor tendon rupture in Kienböck disease 1,2 . In the Lichtman classification, extensor tendon rupture predominantly occurs among older patients with advanced stages, such as stages IIIb or IV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two reviews have previously summarized the characteristics of extensor tendon rupture in Kienböck disease 1,2 . In the Lichtman classification, extensor tendon rupture predominantly occurs among older patients with advanced stages, such as stages IIIb or IV.…”
Section: Discussionmentioning
confidence: 99%
“…Partial or total excision of the displaced fragment is less invasive and is thus the most commonly performed procedure for this condition 1,3,5,[7][8][9][10] . By contrast, partial wrist arthrodesis or PRC is invasive for the wrist and has been reported in a few studies 2,4,6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hernandez-Cortes et al reported that the association between Kienböck disease and tendon rupture may result in delayed treatment and poor prognosis due to improper preoperative imaging and physical examination [ 7 , 9 ]. Tomori et al [ 2 ] reported a ruptured EDC tendon of the ring finger due to Kienböck disease in a patient who delayed treatment for 6 months because she lacked symptoms in her everyday functions.…”
Section: Discussionmentioning
confidence: 99%
“…Kienböck disease results from avascular necrosis of the lunate bone and leads to dislocation of the carpal bone. It can cause closed tendon rupture by attritional injury of the tendon due to a collapsed fragment of the lunate bone [ 2 ]. Closed rupture of the extensor tendons secondary to necrosis and collapse of the lunate bone mainly affects the extensor indicis proprius (EIP) of the index finger and the fourth compartment of the extensor tendons [ 3 ].…”
Section: Introductionmentioning
confidence: 99%